2020
DOI: 10.1111/jspn.12303
|View full text |Cite
|
Sign up to set email alerts
|

Parental mobile health adherence to symptom home monitoring for infants with congenital heart disease during the single ventricle interstage period: A concept analysis

Abstract: Purpose: Single ventricle heart disease is fraught with risk for infant mortality and morbidity. During the interstage period, or the time between palliative cardiac surgeries, mobile health (mHealth) technology improves the ability of registered nurse coordinators to monitor infant symptoms through parental monitoring and reporting. The concept of parental mHealth adherence to symptom home monitoring of infants with single ventricle congenital heart disease has not been defined, despite increasing use of mHea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
(126 reference statements)
0
6
0
Order By: Relevance
“…There has been an increased attention in home monitoring technology and mobile applications over the past several years that have demonstrated promising results (Bingler et al, 2018;Erickson et al, 2020;Foster et al, 2021;Medoff Cooper et al, 2020;Nkoy et al, 2019). There is a need to continue to push the state of the science beyond the advantages in home monitoring to the implementation science aspects of ( 1 There are several limitations of this study.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…There has been an increased attention in home monitoring technology and mobile applications over the past several years that have demonstrated promising results (Bingler et al, 2018;Erickson et al, 2020;Foster et al, 2021;Medoff Cooper et al, 2020;Nkoy et al, 2019). There is a need to continue to push the state of the science beyond the advantages in home monitoring to the implementation science aspects of ( 1 There are several limitations of this study.…”
Section: Discussionmentioning
confidence: 89%
“…There has been an increased attention in home monitoring technology and mobile applications over the past several years that have demonstrated promising results (Bingler et al, 2018; Erickson et al, 2020; Foster et al, 2021; Medoff Cooper et al, 2020; Nkoy et al, 2019). There is a need to continue to push the state of the science beyond the advantages in home monitoring to the implementation science aspects of (1) determining the best way to design home monitoring systems that allow caregivers and patients to actively participate in their data entry and communication with providers, (2) implementation of technology‐enhanced home monitoring that promotes adherence to data entry, and (3) assessment of how technology‐enhanced home monitoring can contribute to clinical‐decision making of providers by responding to changes in patient situations based on established algorithms and nuanced trends in clinical data.…”
Section: Discussionmentioning
confidence: 99%
“…This may promote successful integration into existing services and thereby the adoption among health care professionals [ 13 ]. For parents of the most vulnerable infants, awareness of symptoms might not be enough and the infant’s cardiologist should recommend extending assessments over time [ 32 ]. Whether parents maintain the ability to detect deterioration even if they do not use the app regularly is currently uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Knight and Baber 25 linked comfort and wearability through a 6-dimension scale encompassing emotion, attachment, harm, perceived change, movement, and anxiety. Adherence studies would have greater effect if researchers reported hours per day, days per week, the percent of total possible time wearing the sensor, how the wearable was prescribed for use, 26 wearable technical details, and stakeholder perspectives. 27 Studies specifically assessing wearability in congenital heart disease remain a critical unmet need for technologies intended for at-home use.…”
Section: Patient Challenges In Wearables Use In Congenital Heart Diseasementioning
confidence: 99%